FOREGROUNDING THE IMAGE OF ISLAMIC ARAB NATIONAL IDENTITY - Alkouri, Ahmad Mohd (Advances in Social Sciences Research Journal, 2017)
This research is set to foreground the historical legacy of the Muslim Ummah identity in general and the Arab identity in particular. The paper begins with the history and origin of the Arabs. It focuses on the image of Islamic Arab identity in the present time using scholars. The following questions could be used as a guideline to foreground the reality of the Islamic Arab National Identity: What issues are contested in a Muslim nation generally and the Arab nation particularly? Who are the central participants in these Arab societies and how are their needs addressed? How has the Arab identity gone through various transformations and how has colonial experience affected the Arab world? How does the political identity affect the Arab ethnic identity?